Facility and researches results of the frictional characteristics of metal – irradiated - ceramics pair - Butenko, V.I.; Dubniuk, S.N.; Dyachenko, A.F.; Manuilenko, O.V.; Pavlii, K.V.; Zajtsev, B.V. (Вопросы атомной науки и техники, 2022)
The technique and facility for studying of frictional characteristics of metal – ceramics pair are presented. Parameters of samples irradiation on the helium ions linear accelerator with 0.12 and 4 MeV energies are resulted. Samples from TiO₂ and Al₂O₃ at 0.12 MeV beam energy are irradiated. Damageability and occurrence profiles of target atoms along of helium ions range as sputtering ratios are calculated for the irradiated materials. Dependences of the sputtered atoms quantity on samples depth are resulted. Using this data, calculations on change of samples “superficial” density along of ions range are made. Experimental results of a sliding friction factor measurement depending on cycle’s quantity, temperature and irradiation dose are presented. On the basis of microscopic researches conclusions on influence of an irradiation on frictional characteristics of a metal – ceramics pair are drawn. Представлено методику та установку для вивчення фрикційних характеристик пари метал – кераміка. Наведено параметри опромінення зразків на лінійному прискорювачі іонів гелію з енергіями 0,12 і 4 МеВ та опромінені зразки з TiO₂ і Al₂O₃ при енергії пучка 0,12 МеВ. Для опромінених матеріалів розраховано профілі пошкоджуваності й залягання атомів мішені вздовж пробігу іонів гелію, a також коефіцієнти розпилення. Наведено залежності кількості розпилених атомів від глибини зразків. Використовуючи ці дані, зроблено розрахунки щодо змінення «поверхневої» щільності зразків уздовж пробігу іонів. Представлено експериментальні результати вимірювання коефіцієнта тертя ковзання залежно від кількості циклів, температури й дози опромінення. На основі мікроскопічних досліджень зроблено висновки щодо впливу опромінення на фрикційні характеристики пари метал – кераміка. Представлены методика и установка для изучения фрикционных характеристик пары металл – керамика. Приведены параметры облучения образцов на линейном ускорителе ионов гелия с энергиями 0,12 и 4 МэВ и облучены образцы из TiO₂ и Al₂O₃ при энергии пучка 0,12 МэВ. Для облученных материалов рассчитаны профили повреждаемости и залегания атомов мишени вдоль пробега ионов гелия, a также коэффициенты распыления. Приведены зависимости количества распыленных атомов от глубины образцов. Используя эти данные, произведены расчеты по изменению «поверхностной» плотности образцов вдоль пробега ионов. Представлены экспериментальные результаты измерения коэффициента трения скольжения в зависимости от количества циклов, температуры и дозы облучения. На основе микроскопических исследований сделаны выводы о влиянии облучения на фрикционные характеристики пары металл – керамика.